Prevalence and Interplay between Borderline Personality Disorder and Adverse Childhood Experiences Among Saudi Arabian University Students: A Case Study (International Journal of Child Health and Nutrition, 2024)
Study: Borderline personality disorder (BPD) is a personality disorder characterized by instability in affect regulation, impulse control, and social interactions. There has been a long-term curiosity among researchers about the reasons for underlying BPD. One such implication is Adverse Childhood Experiences (ACE). This study aimed to find out the correlation between BPD and ACE in the context of Saudi Arabian University students. Adverse Childhood Experiences (ACE) play a significant role in the personality traits leading to BPD in adults, and we hypothesize that there is a significant relationship between ACEs and the occurrence of BPD among young college students at King Abdulaziz University. There is very limited published data regarding Gulf countries, including case reports, reviews, and meta-analyses. Material and Methods: The study was conducted among Saudi Arabian University students aged between 18 and 30. This cross-sectional study at King Abdul-Aziz University involved a total of 1970 subjects. The questionnaire comprised sociodemographic characteristics, the Mclean Screening Instrument for BPD (MSI-BPD), and the Adverse Childhood Experiences (ACE) Questionnaire for Adults. Results: Our study found that amongst the total subjects undertaken, 41.2% were at a high risk of developing BPD. This is in direct correlation with 61.4% that suffered previous childhood trauma. Amongst the total subjects undertaken for the study, 43.6% of university students experienced ACE; symptoms were associated with smoking, having at least one family member diagnosed with a mental disorder, being divorced, and having a deceased mother.Conclusion: BPD and ACE are positively correlated, as both have implications for other life-determining factors of the subjects. The study presents the first cross-sectional data set for Saudi Arabian students involving BPD and ACE. This study is significant as it specifically focuses on university students in Saudi Arabia. It suggests that counseling services on all university campuses should be required to facilitate regular evaluation and support for students' mental health.